Public Finance Management: Dynamics of Public-Servant–Political Leadership in the Livestock Sector in Malawi. - Ng'ambi, George; Tembo, Mavuto; Kamtukule, Vera; Shaibu, Benard (Scientific Research Publishing, 2023)
Livestock sector development is vital in the agricultural sector and contributes significantly to the economy. The industry is funded by the public budget, which is a fertile ground for the political economy of the government. This paper examined power dynamics between elected political leaders and public servant leadership in managing public finances. The study used cross-sectional descriptive and exploratory research design with a sample size of 95 respondents to achieve the research objectives. The data collected was analyzed using descriptive and inferential statistics (Chi-Square test and analysis of variance) in SPSS version 20. The results showed that public servants have more authority and control over public finance management. Power in public finance management does not reside in one stakeholder but is volatile. Collaboration between public servant-political existed to achieve set objectives by political and public servant leaders and compliance with the public finance framework. The findings of this study are inferred to some extent from other public sectors in Malawi.
Keywords: Public Finance Management, Public Servant-Political Leadership, Power, Collaboration, and Interest